An analysis of online digital menu design as internal advertising tool to promote an ethnic restaurant in Malaysia / Norsyazana Nazli and Ezlin Sazlin Mohd Annuar - Nazli, Norsyazana; Mohd Annuar, Ezlin Sazlin (2021)
This undergraduate project aims to analyse online menu design as an internal advertising tool to promote an ethnic restaurant in Malaysia. This study used descriptive design from the secondary data analysis for the investigation. The vast use of devices had bounced the restaurant operators to have digital menus as it was easily reachable by the community. Thus, the study on the core component used on digital online menu design is very crucial as it to be used by the restaurant operator for not causing the community to feel confused and misinterpret the theme of their ethnic restaurants.